International investments in private equity : asset allocation, markets, and industry structure - Cornelius, Peter (Burlington, MA : Academic Press, 2011)
The book uses a proprietary database to investigate and describe private equity markets worldwide, revealing their levels of integration, their risks, and the ways that investors can mitigate those risks . It offers hard-to- find analyses that fill knowledge gaps about foreign markets.
Foreword by Lerner josh
Includes bibliographical references (p. [279]-288) and index.
rua 22/05/13
Loans
Keywords: Private equity; Investments, foreign